ANALYSIS OF NEEDS FOR THE DEVELOPMENT OF ETHNOMATHEMATIC E-MODULES BASED ON RIAU MALAY CULTURE TO FACILITATE MATHEMATIC LITERATURE ABILITY OF SMA/MA STUDENTS - Damayanti, Nofita; Roza, Yenita; Maimunah, Maimunah (Jurnal Pendidikan Matematika dan IPA, 2022)
This research aims to determine the needs of teachers and students before the formulation of Riau Malay based ethnomatematics e-module to facilitate student"™s mathematical literacy skills. This research used qualitative descriptive methods that are oriented towards the development of a product. The subject of this research were two mathematics teacher and students of class XI of SMA Nurul Falah Pekanbaru. Data were collected by using interview method and questionnaire distribution. The data obtained were analayzed into three aspects which are analysis of curriculum, analysis of students, and analysis of materials. The result shows that the curriculum that is being used is curriculum 2013. Teaching materials that are being used are textbooks from Erlangga publisher. Result of student"™s analysis shows that 85,7% of students need the exercise about literacy and numeracy in matehmatics subject. 71,4% of students agree that literacy questions in mathematics subjects that contain elements of Riau Malay culture will increase their interest in understanding the problem. The result of this research shows that it is necessary to develop an ethnomathematics e-module based on Riau Malay culture to facilitate student"™s mathematical literacy skills.